An Atlas of catfish brain - Steindachneridion parahybae (Teleostei: Siluriformes): a detailed cytoarchitectonic study of the different brain areas and nuclei as a basis for further morphological and functional studies - Medrado, Andreone Teles (2015)
In the present Master\'s Dissertation, a detailed cytoarchtectonic study of the brain of the juvenile catfish - Steindachneridion parahybae, has been performed. The animals used for this Atlas were juvenile specimens of one hundred days post-fertilization. The coronal (transverse) sections (5µm-thick) were obtained by using a rotary microtome, stained with cresyl-violet and examined under a photomicroscopy with the help of a digital system of analysis. Some criteria have been used to classify the different cell masses of the catfish brain: (i) characteristic size, shape and intensity of the staining from the perykarya; (ii) packing density and distribution pattern of the cell bodies; (iii) neuropil surrounding the cell groups and (iv) consistency of cell groups in both hemispheres and different brains of catfish. Thus, around one hundred and thirty nuclei have been described in the catfish brain, which are distributed in four main region that are from rostral to caudal: telencephalon, diencephalon, mesencephalon and rhombencephalon. Although we have observed important similarities between the brain of catfish and other teleosts, we have also noticed some differences in the characteristics and placement of several nuclei in relation to other teleosts, or even when compared to the brain of species of the same Order, the Siluriformes. Some of these differences could be related with the age of the animals studied here, but probably represent species-specific differences because the brain of adult catfish specimens has a great similarity in cytoarchitecture and overall organization compared to younger animals. The main outcome of this study has been the availability of a complete Atlas of the brain of catfish, which has been used to localize precisely the distribution of cells and fibers of the Gonadotropin-releasing hormone in the brain. This Atlas will also represent a valuable tool for future endocrine analyses, allowing the precise mapping of the different neurohormones in the brain of catfish, as well as for the study of neural connections among different brain areas